The atherogenic index of plasma is associated with an increased risk of diabetes in non-obese adults: a cohort study - Cao, Jun; Su, Zhaohai; Yang, Jiangyong; Zhang, Bilong; Jiang, Rengui; Lu, Weiling; Huang, Zhenhua; Xie, Zheng (Frontiers in Endocrinology, 2025)
ObjectiveThis study aims to investigate the relationship between the atherogenic index of plasma (AIP) and diabetes risk in Chinese non-obese adults. This is important because the incidence of diabetes is significant in non-obese populations, and evidence regarding this association is limited.MethodsWe conducted a retrospective cohort study with 82,977 Chinese non-obese adults. We used Cox proportional hazards regression to assess the relationship between baseline AIP levels and diabetes incidence. We also employed cubic spline functions and smooth curve fitting to investigate potential nonlinear relationships. Sensitivity and subgroup analyses were conducted to validate our findings.ResultsThe median follow-up duration for these participants was 3.10 years, during which 1,041 subjects (1.25%) were diagnosed with diabetes. Adjusted analyses demonstrated a strong positive association between AIP and the risk of diabetes onset (HR 2.07; 95% CI: 1.63-2.63; p < 0.001). The risk of diabetes increased with higher AIP quartiles, especially between the highest (Q4) and lowest (Q1) quartiles (adjusted HR 1.55; 95% CI: 1.27-1.89). We also identified a nonlinear relationship between AIP and diabetes risk. Sensitivity and subgroup analyses confirmed these findings. Furthermore, E-value analysis indicated that the results were robust against unmeasured confounding variables.ConclusionOur findings highlight a positive, nonlinear association between AIP and diabetes risk in Chinese non-obese adults. Lowering triglycerides (TG) or increasing high-density lipoprotein cholesterol (HDL-C) levels may help reduce this risk.